138 Renal outcomes in lupus nephritis randomized controlled trials: a systematic review and a pooled analysis on 3922 patients. (April 2019) - Cecchi, Irene; Radin, Massimo; Menegatti, Elisa; Roccatello, Dario; Sciascia, Savino
Abstract : Background: Systemic lupus erythematosus (SLE) is a complex and potentially life-threatening autoimmune disease characterized by a wide range of manifestations. Renal involvement represents a major cause of morbidity and mortality and lupus nephritis (LN) remains a major therapeutic challenge. 1 Therefore, selecting appropriate outcome measures for clinical trials represent a crucial step in order to identify appropriate drug regimens for LN treatment. The aim of this study was to systematically review the available literature to compare renal primary outcome measures used in randomized controlled trials (RCTs) for both the induction and the maintenance therapy in biopsy proven LN setting. Methods: A detailed literature search was applied a priori to Ovid-MEDLINE (2000–2018), clinicaltrail.gov and to abstracts from the EULAR and ACR/ARHP Annual Meetings (table 1 ). Results: A total of 3922 patients with LN were identified from 28 RCTs. Mean follow-up period was 17.3±15.9 months. Patients were distributed, based on the presence of active biopsy-proven LN, as follow: 717 (23.6%) patients presented class III LN, 1681 (55.3%) class IV, 448 (14.7%) class V, and 195 (6.4%) class IV+V. Twenty-three RCTs (92%) were designed to investigate induction therapy for active LN, while 5 (8%) for maintenance. Twenty-five out of 28 (89.3%) trials considered 'complete remission' (CR) as the primary outcome, and 3 (10.7%) studies used 'time to renal flare/time to treatment failure' as primary endpoint. When analyzing the definition of CR based on the inclusion of urine protein excretion, renal function (including serum creatinine, serum albumine, glomerular filtration rate, and/or estimated glomerular filtration rate), urinary sediment, and the SELENA-SLEDAI, we found that only 1 (4%) trial considered all these variables, 13 (52%) comprehended 3 items, 9 (36%) 2 items, and 2 (8%) included only one variable. In detail, protein excretion was included as a variable computed to define CR in 23 (92%) studies (with range of UPCR raging from 3.2 to 0.3), renal function in 22 (88%), urinary sediment in 13 (52%), and SELENA-SLEDAI in 2 (8%) of the analyzed trials. Conclusions: We report an overall heterogeneity of the primary endpoints used in RTC in LN patients. With the armamentarium of treatments for LN potentially expanding, a better homogeneity in the choice of clinical outcomes is warranted to improve the comparability of the results, potentially leading to a more personalized approach to LN management. Funding Source(s): None Reference: Houssiau FA, Lauwerys BR. Current management of lupus nephritis. BestPract Res Clin Rheumatol 2013;27:31928.